Neural Synchrony During Naturalistic Information Processing Is Associated With Aerobically Active Lifestyle and Cardiorespiratory Fitness in Cognitively Intact Older Adults - Eisenstein, Tamir; Giladi, Nir; Hendler, Talma; Havakuk, Ofer; Lerner, Yulia (Frontiers in Human Neuroscience, 2022)
The functional neural mechanisms underlying the cognitive benefits of aerobic exercise have been a subject of ongoing research during the recent years. However, while most neuroimaging studies to date which examined functional neural correlates of aerobic exercise have used simple stimuli in highly controlled and artificial experimental conditions, our everyday life experiences require a much complex and dynamic neurocognitive processing. Therefore, we have used a naturalistic complex information processing fMRI paradigm of story comprehension to investigate the role of aerobically active lifestyle in the processing of real-life cognitive-demanding situations. By employing inter-subject correlation (inter-SC) approach, we have identified differences in reliable stimulus-induced neural responses between groups of aerobically active (n = 27) and non-active (n = 22) cognitively intact older adults (age 65 - 80). Since cardiorespiratory fitness has previously been suggested to play a key role in the neuroprotective potential of aerobic exercise, we have investigated its dose-response relationship with regional inter-subject neural responses. We found that aerobically active lifestyle and cardiorespiratory fitness were associated with more synchronized inter-subject neural responses during story comprehension in higher order cognitive and linguistic brain regions in the prefrontal and temporo-parietal cortices. In addition, while higher regional inter-SC values were associated with higher performance on a post-listening memory task, this was not translated to significant between-group difference in task performance. We therefore suggest that the modulatory potential of aerobic exercise and cardiorespiratory fitness on cognitive processing may extend beyond simple and highly controlled stimuli to situations in which the brain faces continuous real-life complex information. Additional studies incorporating other aspects of real-life situations such naturalistic visual stimuli, everyday life decision making, and motor responses in these situations are desired to further validate the observed relationship between aerobic exercise, cardiorespiratory fitness, and complex naturalistic information processing.